2014
DOI: 10.1016/j.bbmt.2013.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reconstitution after Haploidentical Hematopoietic Stem Cell Transplantation

Abstract: Haploidentical hematopoietic stem cell transplantation (HSCT) offers the benefits of rapid and nearly universal donor availability and has been accepted worldwide as an alternative treatment for patients with hematologic malignancies who do not have a completely HLA-matched sibling or who require urgent transplantation. Unfortunately, serious infections and leukemia relapse resulting from slow immune reconstitution remain the 2 most frequent causes of mortality in patients undergoing haploidentical HSCT, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
69
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 108 publications
(201 reference statements)
12
69
0
1
Order By: Relevance
“…36 Ciurea et al 37 compared TCR and TCD haploidentical HSCT and found that TCR protocol had a fast immune recovery. This result is in accordance with our data, 7,38 suggesting that a rapid immune reconstitution may contribute to a superior outcome as reported by Ciurea et al 37 Interestingly, healthrelated quality of life in unmanipulated HBMT at our centre is comparable to that in patients receiving HLA-identical sibling allo-HSCT. 39 Furthermore, other factors such as donor age can also be a useful predictive factor.…”
Section: Discussionsupporting
confidence: 93%
“…36 Ciurea et al 37 compared TCR and TCD haploidentical HSCT and found that TCR protocol had a fast immune recovery. This result is in accordance with our data, 7,38 suggesting that a rapid immune reconstitution may contribute to a superior outcome as reported by Ciurea et al 37 Interestingly, healthrelated quality of life in unmanipulated HBMT at our centre is comparable to that in patients receiving HLA-identical sibling allo-HSCT. 39 Furthermore, other factors such as donor age can also be a useful predictive factor.…”
Section: Discussionsupporting
confidence: 93%
“…B-cell recovery was superimposable in TBI and TLI patients. In contrast with what was observed for T-cell subsets, na€ ve B-cell counts recovered before memory B cells as previously reported by other groups of investigators (7,(45)(46)(47), including after HLA-haploidentical stem cell transplantation (48). Specifically, median na€ ve B-cell counts were already within the normal ranges 180 days after transplantation while unswitched memory B cells remained below normal ranges the first year after transplantation in both arms, and switched B cells reached the lower limit of normal values 2 years after transplantation.…”
Section: C-h Recovery Of Cd8supporting
confidence: 78%
“…Considering the effects of recovered immune cells on transplant outcomes reported by others 29 and us, 30,31 our results provide a reasonable explanation for the similarities in clinical outcomes after NIMA-mismatched and NIPA-mismatched unmanipulated HBMT.…”
Section: Cd25supporting
confidence: 82%